187 Systematic Review of Randomized Control Trials to Review the Role of Prebiotics in Prevention of Necrotizing Enterocoloitis in Preterm Newborns. (October 2012) - Ali, S; Faruque, L; Kumar, M
Abstract : Background and aims: Necrotizing enterocolitis (NEC) is an important cause of mortality and serious morbidity in preterm infants. Prebiotics are specific oligosaccharides which have been shown to promote proliferation of beneficial bacteria in gut. This systematic review aims to review the literature to investigate the role of prebiotics in the prevention of NEC in preterm infants. Methods: Electronic databases CSDR-DARE, MEDLINE, CINAHL, EMBASE, Scopus, Web of science were serached from the date of inception to March 27, 2012. Additional citations were retrieved from the bibliography of the selected articles, Google scholarand abstracts of conference proceedings. The eligible studies were RCTs or quasi-RCTs enrolling inpatient preterm infants that compared use of Prebiotics (any dose and duration) with control (placebo/no treatment) for the outcomes of NEC (stage >=2 Bell's classification, perforation and any stage), growth and any other potentially beneficial effect or serious side-effects. Two independent reviewers extracted the data and assessed the risk of bias in included studies. Descripencies were resolved with consensus. Results: 14 studies fulfilled the inclusion criteria. None reported on the primary outcome of stage>=2 NEC. Two RCT reported on NEC (any stage) and showed no significant difference between the groups. There was no difference noted in the growth parameters [(weight & length (3 studies); head growth (2 studies)]. There was a trend towards higher stool frequency (one study) and higher Bifidobacterium count in stool (2 studies) in the Prebiotic group. Conclusion: Current data is insufficient to recommend the use of Prebiotics in preterm infants for prevention of NEC.